Application Of Artificial Intelligance-Based Photography On Ornamental Plants Hobbies For Wives To Reduce The Mental Health Crisis Of Civil Servants - Nuraini Nuraini; allif syahputra bania; Najihatul Faridy; Bachtiar Akob; Teuku Hasan Basri (Journal of Innovative and Creativity, 2025)
The urgency of this research lies in the importance of studying the impact of artificial intelligence (AI)-based ornamental plant photography applications by wives on the mental health of civil servants because the crisis of mental illness such as stress, anxiety, and depression has taken a toll on the psychology and led to physical illness of civil servants in the Unitary State of the Republic of Indonesia. Therefore, this study aims to develop the usefulness of the function of AI-based photography applications to reduce the crisis of mental illness of civil servants through wives' hobbies for ornamental plants which can be an alternative cure. The method in this study uses an ethnographic approach which functions to determine the effect of AI-based photography applications on ornamental plant hobbies by wives in minimizing the influence of mental illness of civil servants in accordance with the views embedded in the minds of the people in Aceh. The steps of the critical ethnographic approach include: determining the research location, determining research informants, interviewing informants, making ethnographic notes, asking descriptive questions, analyzing interview results, submitting domain analysis, utilizing interpretive approaches and critical findings, actively involving participants, and emphasizing reflexivity and ethical responsibility. The conclusion of the study of 50 respondents in the activity of photographing and obtaining information from three types of ornamental plants is that this can suppress mental illness, make people happy, and relieve stress.